Proceedings, Annual General Meeting, 1993 (The Southern African Institute of Mining and Metallurgy, 1993)
The 96th Annual General Meeting of The South African Institute of Mining and Metallurgy was held in the Gold Room of the Transvaal Automobile Club in Johannesburg on Wednesday, 11th August, 1993. OBITUARIES The President announced the deaths of the following members of the Institute during the past year. Life Fellow E.F. Laschinger. Other Members R.K. Boright, J.S. Jacobi, R.D. Power, J.H. Cannon, C.J. du Plooy, L.B. Mcrae, C.P. Rossouw, A.L. Sillars, A.W. Heugh, R.K. Briggs, P.J. Stark, and C.S. Stott. As a mark of respect to the memory of the deceased and in sympathy with the bereaved, all rose and observed a moment of silence.